Promoting Metacognitive Strategies to Listening Class - Sucipto, Sucipto (Ahmad Dahlan Journal of English Studies, 2015)
Listening skill is often ignored. David Nunan (1997) commented that listening is the "Cinderella Skill" which is overlooked by its elder sister "speaking" in SL learning. Speaking and writing skill has become the standard of the knowledge of second language, listening and reading have been turned to be the secondary ones. On the other hand, listening is vital in the language classroom because it provides input for the learner. In fact, most English listening teachers focus on testing learners listening skill rather than on developing the learnersâ listening skill. This practice tends to make them anxious and tends to become ineffective listeners. This condition brings about the learnersâ difficulties in comprehending listening materials. Good English teachers should minimize such a condition. This article attempts to find ways of creating good atmosphere for listening class. What should we âas teachersâ do to respond the problem? Metacognitive is theory of awareness of what and how to learn. Based on my experience in teaching listening, metacognitive strategies are very valuable for learners to learn listening. Finally, I encourage listening class teachers to promote the strategies to their students. To promote the strategies a teacher should do several steps with the class; discussing learnersâ problems, talking the nature of listening, building studentsâ awareness about the important of learning strategies, training the students about metacognitive strategies, and doing reflection. Keywords: Listening, Strategy, MetacognitionÂ